Hubungan antara kebiasaan merokok, sarapan, dan uang saku dengan asupan energi mahasiswa - Kusuma, Rendra; Rahman, Taufik (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2024)
A balanced diet is one of the most important things in maintaining a person's health level and optimal condition, including nutritional status. Many factors are thought to be related to the adequacy level of energy in students. This research aims to determine what factors are related to the energy intake of Physical Education Health and Recreation students, STKIP PGRI Sumenep. Quantitative observational analytics with a cross-sectional study approach was used in this research. The Food Record Questionnaire collects food intake data, including smoking habits, breakfast, and pocket money. The data obtained from the food record is entered into Microsoft Excel 2013. The food consumption data is entered, then the individual's intake and energy adequacy level are calculated.  Spearman rank analysis determined the relationship between smoking habits, breakfast, pocket money, and students' adequacy level of energy. The average energy intake of students is 1138 calories. Most students' adequacy level of energy is classified as lacking. A significant relationship exists between smoking habits, breakfast habits, and pocket money with students' energy intake (p<0.05).